THE EFFECT OF TAXPAYER'S KNOWLEDGE OF TAXATION REGULATIONS, KNOWLEDGE OF INFORMATION SERVICES FOR MOTOR VEHICLE TAX PAYMENT AND POLICE OPERATIONS ON COMPLIANCE WITH COMPLIANCE TAX - Kalisma Ratna Apriani; Icih Icih; Asep Kurniawan (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2019)
Motorized vehicles are one type of local tax, but there are still many taxpayers of motorized vehicles that are not compliant in paying motor vehicle taxes. So efforts are needed that can increase motor vehicle taxpayer compliance, some efforts that can increase vehicle taxpayer compliance are by increasing knowledge about motorized vehicle taxation regulations, knowledge of motor vehicle tax payment services and inspection of police operations. This study aims to determine the influence of knowledge about tax regulations, knowledge of information on motor vehicle tax payment services and police operations on motor vehicle taxpayer compliance. The population used in this study is motor vehicle taxpayers registered in Subang Sub-district Social Security System. The sample selection technique uses incidental sampling. Anyone who happens to meet with a researcher can be used as a sample. The analytical tool used in this study is multiple logistic regression statistical regression. The results of this study indicate that knowledge of motorized vehicle tax regulation has no evidence that it can affect motor vehicle taxpayer compliance, knowledge of motor vehicle tax payment service information there is evidence that it can affect motor vehicle taxpayer compliance, and police operations have no evidence of taxpayer compliance motor vehicle